The greenhouse gas emissions of an electrified vehicle combined with renewable fuels: Life cycle assessment and policy implications. (1st May 2021) - Andersson, Öivind; Börjesson, Pål
Highlights: LCA of the GHG performance of a passenger car with various degrees of electrification. Sensitivity analysis regarding the electricity mix and renewable fuel content. Renewable fuels may lead to lower GHG emissions than a low carbon electricity mix. Both electrification and renewable fuels are needed to reach the sector's climate goals. Policy instruments favor electrification over renewable fuels and need corrections. Abstract: A life cycle assessment is presented for a current vehicle's greenhouse gas impact when using a combination of electrification and renewable fuels. Three degrees of electrification are considered: a hybrid electric vehicle, a plug-in hybrid electric vehicle, and a battery-electric vehicle. These are combined with fuels with various degrees of renewable content, representing a fossil fuel, a first-generation biofuel and a second-generation biofuel. For charging, the 2020 European electricity mix is used and compared with an electricity mix of low greenhouse-gas intensity. Renewable fuels are found to have a greater potential to reduce the life-cycle greenhouse gas emissions than a low carbon electricity mix. The results are discussed in terms of the supply potential for renewable fuels on the fleet level. It is found that plug-in hybrid vehicles may enable the automotive sector to reach more ambitious climate goals than battery-electric vehicles. An assessment is also made of how the life cycle greenhouse gas emissions compare with the emissions as measured by current policy instruments. The discrepancies indicate that current climate policy instruments are inadequate for minimizing the automotive sector's climate impact and suggestions for improvements are made.